Sunset on 17 Mile Drive, Carmel, California. - Pat Palmer:::Creator::::::::::::
A photo of a sunset on 17 Mile Drive in Monterey, California. Enclosed is a Christmas card with descriptions from Pat Palmer, from the Stanford special collections.